2020
DOI: 10.3233/tad-180222
|View full text |Cite
|
Sign up to set email alerts
|

Development of emotional skills through videomodeling: A case study with a non-verbal participant

Abstract: BACKGROUND: Videomodeling is an effective technological tool for intervention and rehabilitation of children with autism spectrum disorders in different contexts. OBJECTIVE: The purpose of this paper is to verify whether a videomodeling intervention is effective for the acquisition of social and emotional behaviour and skills of children with ASD using tablet PC. METHODS: One 6-year-old child with ASD, who does not use verbal communication, was involved in a multiple baseline across behaviours design: the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…One study found that modeling based on recorded self-recordings was associated with faster acquisition of affect recognition and empathic responses skills compared to peer-video recording modeling [ 48 ]. Preliminary studies have found this method was effective in teaching children to recognize and label emotions, even in nonverbal participants [ 49 ]. In addition, prior studies indicated that virtual reality was effective in emotion regulation and management and can also lead to the generalization of skills to nonpracticed situations [ 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that modeling based on recorded self-recordings was associated with faster acquisition of affect recognition and empathic responses skills compared to peer-video recording modeling [ 48 ]. Preliminary studies have found this method was effective in teaching children to recognize and label emotions, even in nonverbal participants [ 49 ]. In addition, prior studies indicated that virtual reality was effective in emotion regulation and management and can also lead to the generalization of skills to nonpracticed situations [ 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several evidence-based practices derived from ABA for teaching prosocial and social behaviors, such as differential reinforcement, naturalistic intervention, social narratives, discrete trial training (DTT), prompting, parental training, and video modeling [11,13,14]. Some of these strategies allow the use of interventions designed to avoid errors or incorrect answers, which is known as errorless learning.…”
Section: Introductionmentioning
confidence: 99%
“…The study’s results suggest that this method could provide a new means for assessing young children with ASD and a starting point for rehabilitation treatments. In another example, Regaa et al [ 7 ] examined the effectiveness of a video modeling intervention for social and emotional behavior and skills in children with ASD using a tablet PC. The study showed a marked improvement in emotional skills, highlighting the potential of video modeling as an effective technological tool for intervention and rehabilitation of children with ASD.…”
Section: Introductionmentioning
confidence: 99%